Healthy Food After COVID-19 Vaccination: Makanan Sehat Paska Vaksinasi COVID-19 - Wahyuningsih, Sri; Abdillah, Achlish; Hayati, Nurul; Sulistyono, R. Endro; Kurnianto, Syaifuddin (KHD Production, 2023)
Coronavirus is a cause of infectious diseases. The European Food Safety Association (EFSA), on March 9, 2020, explained that there is no evidence yet to show that food is part of the coronavirus transmission route (of course, when we consume food in the right and clean way standard). Basic Health Research conducted by the Ministry of Health in 2018 shows that few Indonesian citizens are malnourished or suffer from diabetes. This group risks experiencing fatal health problems when attacked by the coronavirus. The aim of this health promotion is that the post-vaccination participants for COVID-19 in the D3 Nursing Study Program, Faculty of Nursing, University of Jember, Lumajang Campus, have a better understanding of consuming healthy food after the COVID-19 vaccination. The service method uses counseling using lectures, question and answer, and demonstrations with X banner and leaflet media for participants after the COVID-19 vaccination, which was carried out on March 17, 2022, taking place at the D3 Nursing Study Program, Faculty of Nursing, Universitas Jember, Lumajang Campus. The results of this community service activity are likely successful. This can be observed in the level of attendance and the activeness of the participants. This activity took place in an orderly and good manner without experiencing significant obstacles. The follow-up that needs to be done is to continue to provide information on healthy food after the COVID-19 vaccination, so that confusing and untrue news can be suppressed so that the people of Indonesia are free of COVID-19, especially the people of Lumajang.